2003
DOI: 10.1108/09574090310806558
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Management as a Competitive Advantage in the Spanish Grocery Sector

Abstract: Adversarial relationships have long dominated business relationships, but Supply Chain Management (SCM) entails a new perspective. SCM requires a movement away from arms-length relationships toward partnership style relations. SCM involves integration, coordination and collaboration across organisations and throughout the supply chain. It means that SCM requires internal (intraorganisational) and external (interorganisational) integration. This paper analyses the relationship between internal and external inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 8 publications
9
105
0
6
Order By: Relevance
“…Flynn et al (2010) state that it is unclear whether the relationship between SCI and performance is the same in different countries or industries. For example, in the car industry, external integration does not lead to a competitive advantage because it is a prerequisite to survive, and almost all companies have implemented it (Gimenez and Ventura 2003). Hence, SCI studies in specific country and industry employing the same SCI dimensions and variables are required in order to achieve comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Flynn et al (2010) state that it is unclear whether the relationship between SCI and performance is the same in different countries or industries. For example, in the car industry, external integration does not lead to a competitive advantage because it is a prerequisite to survive, and almost all companies have implemented it (Gimenez and Ventura 2003). Hence, SCI studies in specific country and industry employing the same SCI dimensions and variables are required in order to achieve comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that high competitiveness can directly improve performance (Suhong Li et al, 2006;Gimenez & Ventura, 2003;2005;Soo W. Kim, 2006a;Rajesh & Margaret, 2009;Glenn Richey et al, 2009). However there are still mixed findings on the impact of competitiveness on company performance (Ting Chi et al, 2009;Soo W. Kim, 2006b), since some studies shows that competitiveness do not have significant impact on performance for small companies and has significant impact only for big companies.…”
Section: Introductionmentioning
confidence: 94%
“…Stank et al, (2001) also supported the link between internal and external integration. Even though studies of internal integration are relatively new in the supply chain context (Giménez, 2004;Giménez and Ventura, 2003;Pagell, 2004), there have been many earlier studies in the area of inter-functional integration in the contexts of new product development and the productionmarketing interface (e.g. Calantone et al, 2002;Kahn, 1996;Kahn and Mentzer, 1996;Mollenkopf et al, 2000;Stank et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%